The Analysis of Students’ Rakat Mufakat Character Through the Application of Local Wisdom-Integrated Module on Heat and Temperature Topic - Resy Resy; Mustika Wati; Misbah Misbah (Universitas Lambung Mangkurat, 2021)
Rakat mufakat is defined as a form of unity in social life which goes hand in hand with deliberation. This descriptive quantitative study aimed to describe the character of rakat mufakat owned by students by applying a local wisdom-integrated module on heat and temperature topic. The research subject was 25 students of class X-6 in SMA Negeri 1 Angkinang, Kandangan city, which was assigned by using purposive sampling technique. The attainment of rakat mufakat character was analyzed by observation sheet filled out by two observers. The character of rakat mufakat consist of tolerance, democracy, and communicative. The measured indicators in this study were giving opportunities to state opinion, willing to accept different opinion, adapting to deliberation, and giving opinions while working in team. Generally, the attainment of rakat mufakat character in the form of average score was 3,47 with the percentage of 87% categorized as very good, while the attainment of rakat mufakat character in every meeting kept increasing with the attainment of 10% categorized as sufficient, 31% categorized as good, and 59% categorized as very good. It shows that the application of local wisdom-integrated module on heat and temperature topic can train the character of rakat mufakat to students. The insertion of the character is important to conserve local cultural values.